IMPLEMENTATION OF FUZZY LOGIC ON SIMULATION OF PH, TEMPERATURE, AND DISSOLVED OXYGEN MONITORING SYSTEM FOR DISCUS FISH - Farhan Adha; Yassar Ariq Pradian; Muhammad Faiz Assariy; Hafiz Kurniawan; Fahmi Fadillah; Dimas Muhammad Fathur Rifki; Kevin Soerhensen; Baihaqi Al Faatih; Ridwan Kuasa Samudra Singajaya; Abu Dzar Al-Ghifari; Fauziah Prima Aulia; Rachel Delamaya Fefriani; Shabrina Kesya Azizah; Larisa Syafa Adisti; Muhammad Rafa Najwan; Daffa Zulqisthi (Batrisya Education, 2025)
Discus fish (Symphysodon spp.) are ornamental fish that require special attention to water quality, including pH, temperature, and dissolved oxygen (DO). This research aims to develop a fuzzy logic-based water quality monitoring system to accurately evaluate these parameters. Quantitative methods were used with data collection through literature review and analysis using Matlab. The fuzzification process is applied to convert numerical data into linguistic values that can be processed by the fuzzy system. Results showed ideal temperature ranged from 27-32°C, optimal pH between 4.0-8.0, and good DO levels between 4.0-6.5 mg/L. The developed fuzzy logic system produced ea water quality assessment with a value of 6.61, indicating a fair quality. With high accuracy and average error less than 5%, the system is effective in decision-making for discus fish rearing. The integration of fuzzy logic technology strengthens the continuous monitoring of water quality. This research shows that a fuzzy logic-based approach can improve water quality management and support discus fish welfare.